Pension accounting disclosures: Actuarial gains and losses and market price reactions - Nora Fauzana, Zainal (2016)
This paper seeks to investigate the market price reactions towards actuarial gains and losses (AGL) disclosure and the determinants of Cumulative Average Abnormal Return (CAAR) by using Cumulative Market Adjusted Return Model (CMAR) and efficient market theory among 86 company-years in Malaysia that has disclosed AGL in annual report for the year 2012 until 2014. The finding shows that there is a negative reaction of CAAR before the financial year ended of AGL disclosure as the information has been spread before the financial year ended. However, the positive market price reaction on and after the financial year ended indicates that the announcement is most welcomed by the investors. Besides, the actuarial losses (AL) are more likely to have significant market price reaction as compared to actuarial gains (AG). It indicates that the investor and shareholder of the company may react immediately towards AL disclosure rather than AG and maybe the investors seem to be conservatism in making their investment decisions. In addition, the study found significant negative relationship between CAAR and AGL disclosures. This finding indicates that investors are more looking for AL disclosures rather than AG disclosures where the actuarial losses disclosures give significant negative market price reactions.